Opportunities of one-dimensional van der Waals materials and heterostructures as fuel cell catalyst layers - Miaoyu Lu; Ziang Chen; Jingyu Sun; Rong Xiang (Carbon Future, 2025)
Fuel cells (FCs) have attracted considerable attention as one of the environmental-friendly energy conversion systems. Strenuous efforts have been devoted to addressing challenges in the catalyst layers (CLs), mainly pertaining to the redox kinetics, mass transport, water management, and mechanical durability. As an emerging direction, one-dimensional (1D) van der Waals (vdW) materials and heterostructures have demonstrated great potential in electronic devices. Their remarkable characteristics, including high electrical conductivity, superior thermal property, outstanding mechanical strength and rigidness, nanoscale curvature, and nearly infinite atomic combination, hold promise for overcoming these challenges. Despite their promising attributes, research on the applications of 1D vdW materials and heterostructures in FCs remains in its infancy, let alone comprehensive reviews targeting this area. Inspired by these considerations, this review summarizes the key properties of 1D vdW materials and heterostructures that underpin their potential applications in CLs. Design strategies of 1D vdW heterostructures are also proposed. Finally, future research directions are outlined to foster the advancement of 1D vdW materials and heterostructures in FCs and energy devices.